Effect of Abrasive Concentration on Impact Performance of Abrasive Water Jet Crushing Concrete - Xiaohui Liu; Ping Tang; Qi Geng; Xuebin Wang (Shock and Vibration)
It has been found that the impact performance of water jets can be changed by its properties, which include pressure, additive, and mode of jet. Thus, an abrasive water jet (AWJ) has been developed as a new method. However, there is little research on the effect of abrasive concentration on the impact performance of abrasive jets. Thus, the SPH method is used to establish an abrasive water jet crushing concrete model to study the effect of abrasive concentration on the impact force, concrete internal energy, abrasive particle distribution, crushing depth, and damage and crushing efficiencies under different concrete compressive strengths and abrasive densities. The results indicate that there is little effect of the abrasive concentration on the peak impact force under different compressive strengths and abrasive densities, while the mean impact force tends to increase linearly with the abrasive concentration. The internal energy of the concrete increases stepwise with the abrasive concentration under different compressive strengths and abrasive densities. The concentration of 10%∼20% is the rapid increasing stage. The crushing depth and damage efficiencies are all maximum at a concentration of 20% under different compressive strengths and abrasive densities. After the concrete was impacted by the water from the water jet, it is divided into rebounding particles and intrusive particles. The more the intrusive particles, the easier the concrete to be crushed and damaged.